A novel and effective approach of developing aggressive experimental autoimmune gastritis in neonatal thymectomized BALB/c mouse by polyinosinic:polycytidylic acid - KOBAYASHI, Y (Blackwell Science Inc, 2004)
Neonatal thymectomy induces autoimmune gastritis (AIG) in 40–70% of BALB/c mice. We presumed that induction of autoimmunity by polyinosinic:polycytidylic acid (poly I:C) might allow development of a more aggressive model of AIG. A group of BALB/c mice were thymectomized on day 3 after birth. Neonatal thymectomized mice were either injected with poly I:C or phosphate-buffered saline (PBS). Non thymectomized neonatal BALB/c mice were injected with only poly I:C. All neonatal thymectomized mice injected with poly I:C developed 3 cardinal features of AIG: (1) moderate to severe degree gastritis (2) presence of autoantibody to H(+)/K(+) ATPase and (3) loss of parietal cells. However, only 70% of the PBS-treated neonatal thymectomized BALB/c mice developed some, but not, all features of AIG. A mild degree of AIG was seen in 12 of 31 nonthymectomized BALB/c mice administered with only poly I:C. Administration of poly I:C in neonatal thymectomized BALB/c mice in the first and second week appeared to be the most effective for induction of aggressive AIG. The levels of interleukin (IL)-6, IL-12p70, interferon-γ and tumour necrosis factor-α were significantly higher in poly I:C-injected thymectomized mice compared to PBS-injected neonatal thymectomized mice (P < 0·05). The frequencies of CD4(+)CD25(+) regulatory T cells in the spleen were significantly decreased in neonatal thymectomized mice administered with poly I:C compared to PBS-treated neonatal thymectomized mice (P < 0·01). Taken together, these results suggest that induction of inflammatory cytokines and reduction of regulatory T cells by poly I:C might contribute to the development of an aggressive model of AIG in neonatal thymectomized BALB/c mice.